2005
DOI: 10.1016/j.neuron.2005.04.007
|View full text |Cite
|
Sign up to set email alerts
|

The Molecular Basis of Odor Coding in the Drosophila Larva

Abstract: We have analyzed the molecular basis of odor coding in the Drosophila larva. A subset of Or genes is found to be expressed in larval olfactory receptor neurons (ORNs). Using an in vivo expression system and electrophysiology, we demonstrate that these genes encode functional odor receptors and determine their response spectra with 27 odors. The receptors vary in their breadth of tuning, exhibit both excitation and inhibition, and show different onset and termination kinetics. An individual receptor appears to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

26
363
4

Year Published

2005
2005
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 290 publications
(393 citation statements)
references
References 51 publications
26
363
4
Order By: Relevance
“…3D and Movie S3). The rest of the DOG neurons-olfactory receptor neurons (ORNs) and a few gustatory receptor neurons-send their dendrites to a dome of cuticle perforated by pores (25). In contrast, the thermosensory neurons develop large membrane-rich dendritic bulbs that appear 60 ± 13% of the distance before reaching the dome (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…3D and Movie S3). The rest of the DOG neurons-olfactory receptor neurons (ORNs) and a few gustatory receptor neurons-send their dendrites to a dome of cuticle perforated by pores (25). In contrast, the thermosensory neurons develop large membrane-rich dendritic bulbs that appear 60 ± 13% of the distance before reaching the dome (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, a learning index of zero indicated that no associations were formed, whereas a learning index significantly greater than zero indicated a positive association between conditioned stimuli and reward. PA and BUT were chosen, as they were unlikely to be odor equivalents; in larvae they are detected and processed by different combinations of peripheral and central structures (Kreher et al 2005). In addition, we found that larvae of the natural rover (for R ), sitter (for s ), and sitter mutant (for s2 ) strain, which was generated on a rover genetic background (de Belle et al 1989;Pereira and Sokolowski 1993), do not differ significantly in their response to these odors (below).…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, the arbovirus vector mosquito Aedes aegypti expresses 24 odorant receptor (OR) genes in the larval antenna, 15 of which are larval specific (4). Elegant work in the Drosophila melanogaster model has detailed larval behavioral responses and characterized 25 ORs that are expressed in 21 olfactory receptor neurons (ORNs) in each of the two dorsal organs, which constitute the olfactory apparatus of the fly larva (5)(6)(7).…”
mentioning
confidence: 99%